Design of organic supercapacitors with high performances using pore size controlled active materials - Yang, Inchan; Kwon, Dahye; Yoo, Jihoon; Kim, Myung-Soo; Jung, Ji Chul (Current applied physics, 2019)
In this study, we thoroughly investigate the required properties of active materials for organic supercapacitors with high performances. In this regard, we synthesize carbon xerogels with different physical properties, including specific surface area and pore size. The carbon xerogels are prepared via the sol-gel reaction of resorcinol and formaldehyde under different gelation temperature conditions. Through Fourier-transform infrared, nitrogen adsorption–desorption, and scanning electron microscopy analysis, we can confirm that carbon xerogels with different physical properties can be successfully synthesized. We apply the prepared carbon xerogels to organic supercapacitor electrodes. As a result of electrochemical experiments, carbon xerogels with high surface area exhibit high electrochemical performances at low-rate charge−discharge processes. However, as the charge–discharge rate increases, carbon xerogels with low surface area and high conductivity exhibit higher performances. Therefore, the surface area of active materials is a key factor for supercapacitors with high performances at low-rate charge–discharge processes. However, the effects of conductivity can be more crucial as compared with those of surface area as the charge–discharge rates increase. In addition, we suggest that the physical properties of active materials should be differently optimized as the charge–discharge rate is employed. •Carbon xerogels with different physical properties were successfully prepared.•The carbon xerogels were applied to active materials of supercapacitors.•Effects of physical properties of active materials were investigated.•Surface area is a crucial factor for low-rate charge–discharge processes.•Conductivity is a crucial factor for high-rate charge–discharge processes.